2002
DOI: 10.1002/jmv.10183
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human herpesvirus 8 DNA in serum from blood donors with HHV‐8 antibodies indicates possible bloodborne virus transmission

Abstract: Human herpesvirus 8 (HHV-8) is associated with Kaposi's sarcoma. There is a high seroprevalence of HHV-8 in several African countries, but the transmission route is not known definitively. In this study 174 serum samples from blood donors in Tanzania were examined by immunofluorescence assays detecting antibodies to latent and lytic HHV-8 antigens. Real-time polymerase chain reaction was used for detection and quantification of HHV-8 DNA in serum. In all, 83/174 (48%) of the subjects had antibodies to latent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 23 publications
(28 reference statements)
10
39
1
1
Order By: Relevance
“…The mean age of 34.7 years with male predominance was reported by Lager et al 21 Male KS predominance has also been reported in other studies. 22,23 Despite the findings of this study concurring with mean age of occurrence of KS to other African studies, there was slight female predilection in our study, with male to female ratio (M:F) of 1:1.7. The gender differences in KS are of interest considering previous suggestions of lower female risk, possibly attributed to hormonal factors including human chorionic gonadotropin in pregnant women.…”
Section: Discussionsupporting
confidence: 72%
“…The mean age of 34.7 years with male predominance was reported by Lager et al 21 Male KS predominance has also been reported in other studies. 22,23 Despite the findings of this study concurring with mean age of occurrence of KS to other African studies, there was slight female predilection in our study, with male to female ratio (M:F) of 1:1.7. The gender differences in KS are of interest considering previous suggestions of lower female risk, possibly attributed to hormonal factors including human chorionic gonadotropin in pregnant women.…”
Section: Discussionsupporting
confidence: 72%
“…Considering the detection rate of the PBMC genome (about 1.33%-22.5%), both domestically and internationally, this provides further evidence that Xinjiang is a high-prevalence area for KSHV. As previously reported, KSHV DNA positive rates were 4.5% and 22.5% among donors in Tanzania (Enbom et al, 2002) and Central Africa (Belec et al, 1998). According to another report, the detection rate of KSHV DNA in 59 blood donors in Italy was 9% (Bigoni et al, 1996).…”
Section: Discussionsupporting
confidence: 68%
“…Alternatively, other factors involved in needle-sharing and promiscuous sexual habits might facilitate HHV-8 acquisition, implying that these women might not represent as homogeneous a population for HHV-8 transmission as for HIV-1 infection. Further studies are needed to clarify the importance of blood-borne HHV-8 transmission, that might be relevant in areas with high HHV-8 seroprevalence in the general population [Belec et al, 1988;Enbom et al, 2002].…”
Section: Discussionmentioning
confidence: 98%
“…While parenteral transmission is not regarded as an efficient mode of HHV-8 spread [Operskalski et al, 1997;Whitby et al, 1998;Engels et al, 1999;Gnann et al, 2000;Challine et al, 2001], infection through the administration of blood/blood products has to be differentiated from infection through needlesharing. In the first case, several variables (lack of viremia in healthy donors, possible depletion of HHV-8-infected lymphocytes, pre-treatment and storage of blood that might reduce virus infectiousness) may limit HHV-8 spread through blood transfusions [Enbom et al, 2002]; these factors are not relevant to needle-sharing. Alternatively, other factors involved in needle-sharing and promiscuous sexual habits might facilitate HHV-8 acquisition, implying that these women might not represent as homogeneous a population for HHV-8 transmission as for HIV-1 infection.…”
Section: Discussionmentioning
confidence: 98%